Pengaruh Nutrisi Organik Cair terhadap Pertumbuhan dan Kelayakan Finansial Bibit Cabe Merah Keriting (Capsicum annuum L.) - Cahyaningtyas Putri Suhita; Desy Setyaningrum; Febry Nurhidayati; Anditya Gilang Rizky; Edi Paryanto; Hardian Ningsih; Didik Suryadi; Dewi Nawang Suprihatin; Zainal Arifin; Dimar Hantari; Wiwid Wulandari (Universitas Gadjah Mada, 2026)
The cultivation of curly red chili peppers in Central Java has experienced a decline due to several factors, one of which is seedling quality. This study aimed to analyze the effect of nutrient application and the feasibility of farming practices in curly red chili pepper seedling production. The research was conducted in Jumantono District, Karanganyar Regency, in June 2025 under tropical microclimatic conditions, with average air temperatures ranging from 22–31 °C and monthly rainfall of approximately 150–200 mm. The experimental design employed a one-factor Randomized Block Design (RBD) with variations in rice washing water nutrient concentrations, consisting of 0 ml (control), 5 ml, and 10 ml, each replicated three times. The application of rice washing water nutrients affected seedling height growth at both the third and sixth weeks after planting. The treatment did not significantly influence stem diameter or leaf number but had a significant effect on seedling height at the third and sixth weeks. The feasibility analysis of curly red chili pepper seedling farming indicated that the application of rice washing water at a dose of 10 ml yielded the most optimal results in terms of profitability and cost efficiency, suggesting its potential as a simple and economical alternative nutrient source for improving seedling quality.